Human endometrium-derived mesenchymal stem/stromal cells application in endometrial-factor induced infertility - Bausyte, Raminta; Vaigauskaite - Mazeikiene, Brigita; Borutinskaite, Veronika; Valatkaite, Elvina; Besusparis, Justinas; Valkiuniene, Ruta Barbora; Kazenaite, Edita; Ramasauskaite, Diana; Navakauskiene, Ruta (Frontiers in Cell and Developmental Biology, 2023)
Endometrial-factor induced infertility remains one of the most significant pathology among all fertility disorders. Stem cell-based therapy is considered to be the next-generation approach. However, there are still issues about successfully retrieving human endometrium-derived mesenchymal stem/stromal cells (hEnMSCs). Moreover, we need to establish a better understanding of the effect of hEnMSCs on the endometrial recovery and the clinical outcome. According to these challenges we created a multi-step study. Endometrium samples were collected from females undergoing assisted reproductive technology (ART) procedure due to couple infertility. These samples were obtained using an endometrium scratching. The hEnMSCs were isolated from endometrium samples and characterized with flow cytometry analysis. Groups of endometrium injured female mice were established by the mechanical injury to uterine horns and the intraperitoneal chemotherapy. The hEnMSCs suspension was injected to some of the studied female mice at approved time intervals. Histological changes of mice uterine horns were evaluated after Masson’s trichrome original staining, hematoxylin and eosin (H&E) staining. The fertility assessment of mice was performed by counting formed embryo implantation sites (ISs). The expression of fibrosis related genes (Col1a1, Col3a1, Acta2, and CD44) was evaluated by the reverse transcription—quantitative polymerase chain reaction (RT-qPCR). Results showed that endometrium scratching is an effective procedure for mesenchymal stem/stromal cells (MSCs) collection from human endometrium. Isolated hEnMSCs met the criteria for defining MSCs. Moreover, hEnMSCs-based therapy had a demonstrably positive effect on the repair of damaged uterine horns, including a reduction of fibrosis, intensity of inflammatory cells such as lymphocytes and polymorphonuclear cells (PMNs) and the number of apoptotic bodies. The injured mice which recieved hEnMSCs had higher fertility in comparison to the untreated mice. Gene expression was reflected in histology changes and outcomes of conception. In conclusion, hEnMSCs demonstrated a positive impact on endometrium restoration and outcomes of endometrial-factor induced infertility. Further exploration is required in order to continue exploring the multifactorial associations between stem cell therapy, gene expression, endometrial changes and reproductive health, so we can identify individually effective and safe treatment strategies for endometrial-factor induced infertility, which is caused by mechanical effect or chemotherapy, in daily clinical practise.